Factors Affecting Consumer Interest In Purchasing Decisions At Sentral Cell Lubuk Linggau Shop - Mira Andina; Ida Anggriani; Nia Indriasari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
Purchasing decision is the final stage of consumers in determining or knowing a product and will decide to buy the desired product.This study aims to determine the effect of transactional interest, referential interest, preferential interest and explorative interest together on consumer interest in smartphone purchasing decisions at the Lubuk Linggau Cell Central Store. The population in this study were buying smartphones at the Lubuk Linggau Cell Central Store and the sample in this study were 50 customers who purchased smartphones at the Lubuk Linggau Cell Central Store. Data collection used instruments in the form of questionnaires and the analytical method used was multiple linear regression, determination test and hypothesis testing.Research results The regression equation obtained is as follows: Y = 9,747 + 0,897 X1 + 0,832 X2 + 0,776 X3 + 0,890 X4 + e 1,820 means that if there is an increase in Transactional Interest, Referential Interest, Preferential Interest, Explorative Interest will also affect purchasing decisions. Transactional interest influences purchasing decisions. Transactional Interest (X1), shows t count of 2.954 > t table 1.66140 significant 0.000 < 0.050, Transactional Interest variable has a positive and significant effect on purchasing decisions. Referential Interest Variable (X2), shows t count of 2.525 > t table 1.66140 with a significant level of 0.014 <0.050. Referential Interest variable has a positive and significant effect on purchasing decisions. Preferential interest influences purchasing decisions. Preferential Interest Variable (X3), shows t count of 2.344 > t table 1.66140 with a significant level of 0.000 <0.050. Preferential interest has a positive and significant effect on purchasing decisions. Explorative interest influences purchasing decisions. Explorative interest (X4), shows t count of 2.980 > t table 1.66140 with a significant level of 0.000 <0.050. Explorative interest has a positive and significant effect on purchasing decisions.